Study on Technical Parameters of X-ray Stereoscopic Imaging of Ablative Defects for Water Blocking Buffer Layer in High Voltage Cable. Issue 1 (1st December 2022) - Xie, Yi; Liu, Jianjun; Feng, Chao; Zhang, Jun; Liu, Sanwei; Chen, Dabing
Abstract: In this paper, the technical parameters of the X-ray stereoscopic imaging of the ablative defects of water blocking buffer layer in the high-voltage cable are studied by theoretical analysis and laboratory experiment. The works give technical recommendations about the voltage, current, and sampling volume, which provide a reference for the standardization of the technical parameters of X-ray stereoscopic imaging of ablative defects of the water-blocking buffer layer in the high-voltage cable.